Analysis of apoptosis induced by bovine gammaherpesvirus 4 in primary culture of bovine endometrial cells - Romeo, Florencia (2021)
BoHV-4 is tropic for bovine endometrium being increasingly considered as responsible for reproductive tract problems during postpartum period in concomitance with gramnegative bacteria. Some gammaherpesviruses, including BoHV-4, carry genes that can inhibit or induce apoptosis. BoHV-4 has two genes that encode proteins (v-Bcl2 and v-Flip) with anti-apoptotic functions. However it was shown that, the induction of apoptosis in vitro by BoHV-4 depends not only on the dose of the viral inoculum and the time of infection, but also on the nature of the infected cells. The objective of this work was to study apoptosis induced by BoHV4 and lipopolysaccharide (LPS) in primary culture of bovine endometrial cells.